Serial Murders in Hatay Case Series - Ortanca, İbrahim; Demirkıran, Dua Sumeyra; Çelikel, Adnan; Arslan, Muhammet Mustafa (The Bulletin of Legal Medicine, 2015)
There is not any case report in Turkey on serial murders. In this paper, we aim to present a serial murder case in which five people were killed in a row of three different incidents, and discuss it comparing with literature.In the first incident, a man making love with a woman in his car was shot dead by two men one with mask, while the woman was released. The second and third events occurred also in the same manner however both men and women were killed. All five victims were killed in their cars at a desolate area and they were fired from outside the car. All were making love witli their partners in the car atthat momentTherefore these five murders are included in the definition of serial murder “unlawful killing of two or more victims by the same of fender (s) in separate events”. According to characteristics of suspects and common features of victims, murders can be classified as “mission” or “visionary” type.Keywords: Serial murders, Hatay, Turkey, Forensic medicine.
Keywords: serial murders; Hatay; Turkey; forensic medicine